Factors associated with recently acquired hepatitis C virus infection in people who inject drugs in England, Wales and Northern Ireland: new findings from an unlinked anonymous monitoring survey. (14th August 2014) - Cullen, K. J.; Hope, V. D.; Croxford, S.; Shute, J.; Ncube, F.; Parry, J.V.
SUMMARY: Monitoring infections and risk in people who inject drugs (PWID) is important for informing public health responses. In 2011, a novel hepatitis C antibody (anti-HCV) avidity-testing algorithm to identify samples compatible with recent primary infection was introduced into a national surveillance survey. PWID are recruited annually, through >60 needle-and-syringe programmes and prescribing services. Of the 980 individuals that could have been at risk of HCV infection, there were 20 (2%) samples that were compatible with recent primary infection. These were more common among: those imprisoned ⩾5 times [8/213; adjusted odds ratio (aOR) 8·7, 95% confidence interval (CI) 2·04–37·03]; women (8/230; aOR 3·8, 95% CI 1·41–10·38); and those ever-infected with hepatitis B (5/56; aOR 6·25, 95% CI 2·12–18·43). This study is the first to apply this algorithm and to examine the risk factors associated with recently acquired HCV infection in a national sample of PWID in the UK. These findings highlight underlying risks and suggest targeted interventions are needed.